Distributed Campus Time Attendance System: k-Kedatangan - Nasrudin, Abd Shukor; Nor Shubaily, Khamis; Mohd Noorulfakhri, Yaacob (Kementerian Pengajian Tinggi Malaysia, 2010)
En. Nasrudin and his team won silver for Distributed Campus Time Attendance System: k-Kedatangan at IPTA R&D Expo 2005, 30th September - 2nd October 2005 organized by Ministry of Higher Education (MOHE) hosted by Universiti Teknologi Malaysia (UTM).